Protective Effect of Betulinic Acid Administration on Kidney Damage in Acetaminophen-Induced Nephrotoxicity Model - Dokumacioglu, Eda; İskender, Hatice; Hayirli, Armagan; Yenice, Guler; Kapakin, Kubra Asena Terim; Bolat, Ismail; Kirman, Esra Manavoglu (Makara Journal of Health Research, 2023)
Background: Acetaminophen (APAP) is the most widely used analgesic drug worldwide, but it may induce renal toxicity. Betulinic acid (BA) ameliorates the oxidative stress and inflammatory response to renal damage. The present study aimed to investigate the potential protective effects of BA treatment through an experimental kidney damage rat model administered with APAP. Methods: Sprague–Dawley male rats were randomly divided into four groups: control, BA (25 mg/kg for 15 days), APAP (1 g/kg), and APAP + BA groups. BA was administered via oral gavage at a dose of 25 mg/kg for 15 days. APAP was dissolved in hot saline and administered on the last day to produce nephrotoxicity via a single oral gavage at a dose of 1 g/kg. Kidney tissue samples were analyzed for human cartilage glycoprotein 39 (YKL-40), kidney injury molecule 1 (KIM-1), interleukin 18 (IL-18), superoxide dismutase (SOD), and malondialdehyde (MDA). Data were subjected to one-way analysis of variance and the Wilcoxon rank-sum test Results: Renal tissue YKL-40, KIM-1, IL-18, and MDA levels in the APAP group were significantly higher than those in the control group (p < 0.05). The BA treatment completely restored renal KIM-1, YKL-40, and MDA levels and partially restored renal IL-18 and SOD levels in the rats subjected to renal damage induction (p < 0.05). The intertubular regions of rats administered with APAP had degeneration, necrosis, and infiltration of inflammatory cells and were immunopositive for IL-1 beta and 8-hydroxy-2′-deoxyguanosine. Conclusions: BA can be used in the prevention and replacement treatment of nephrotoxicity due to its inhibitory properties in multiple pathways and powerful antioxidant effects.